A gyepek helyreállításának lehetőségei különböző élőhelyeken, különböző legelő állatokkal: Áttekintő esettanulmányok III: Juhlegelők - Penksza, Karoly; Pajor, Ferenc; Wagenhoffer, Zsombor; Szabo-Szollosi, Tunde; Salata-Falusi, Eszter; Sari, Leonard; Balogh, Janos; Szoke, Peter; Penksza, Peter; Poti, Peter; Salata, Denes; Balogh, Petra; et al. (Gyepgazdálkodási Közlemények, 2025)
From a land-use perspective, sheep grazing is primarily justified on sites of lower soil productivity. This is due to the grazing behaviour of sheep, characterised by selective feeding and close cropping. Such grazing promotes the development of a diverse vegetation structure, which is of high conservation value. However, under prolonged overgrazing, undesirable plant species may proliferate within the sward. The present review seeks to identify, in general terms, which species tend to become dominant on sheep pastures and which species are likely to spread under intensive grazing. Investigations carried out across several Hungarian landscape types yielded comparable results. Under high grazing pressure, Lolium perenne, Cynodon dactylon and Hordeum hystrix typically became dominant. By contrast, under low grazing pressure, Festuca pseudovina was generally found to prevail.